Survey of trainers on the use of swimming exercise for Standardbred racehorses in Australia. Issue 3 (26th February 2019) - Steel, CM; Bond, BM; Morrice‐West, AV
Abstract : Objectives: To determine swimming training practices in Australian harness racing horses and potential targets for future research. Methods: An online survey of Australian Standardbred trainers and telephone interviews with 20 leading trainers were conducted. Questions relating to swimming facility and protocol, perceived benefits and contraindications were included. Descriptive data analysis was performed. Results: Data were collected from 270 trainers: 250 by online survey (250/1770, response rate 14.1%) and 20 by interview. Of these, 103 trainers (38.1%), including 91 surveyed trainers (91/250, 36.4%) and 12 interviewed trainers (12/20, 60.0%), used swimming exercise. The most popular reasons for swimming were to replace trackwork for horses with limb injuries (79.4%), improve or maintain fitness (62.7%) and provide mental stimulation through variety in training (40.0%). Free swimming (78.4%) was more common than tethered, but the frequency and duration for horses in full training varied widely between trainers, with a median of four swim sessions per horse each week (range 0.5–12) for a median of 7 min (range 1.5–30 min) per session, mostly as a continuous swim, but sometimes as intervals. The main reasons given by those not swimming horses were lack of an adequate facility (60.5%) and lack of perceived benefit (16.2%). Reasons for not swimming individual horses varied widely. Conclusions: Trainer opinions and protocols varied widely with respect to swimming exercise for Standardbred race horses. The role of swimming exercise requires further study so that evidence‐based recommendations can be made.